2018
DOI: 10.1111/eff.12417
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in fish community structure and diversity in the largest tropical flood‐pulse system of South‐East Asia

Abstract: The Tonle Sap River and Lake (TSRL) is South-East Asia's largest tropical flood pulse with a flow-reversal system that supports one of the world's largest freshwater fisheries. However, among the world's tropical floodplains, the resources of the TSRL have received little ecological research. Here, we described the spatiotemporal TSRL fish diversity and community variation using daily records from 2012 to 2015 on fish abundance from six sites covering the TSRL system. We found that high fish diversity occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 42 publications
4
30
0
Order By: Relevance
“…Similarly, climate change likely affected fish distributions, and as demonstrated here, temperature and precipitation likely affected different species in different manners. However, as indicated in our discussion, our results are still consistent with some recent studies examining the fish distribution patterns, diversity and assemblage structure in the TSL, e.g., [12,19] and elsewhere, such as in the floodplain-lake of the Amazon, where fisheries yields were significantly varied in accordance with the amount of flooded forest habitats [68]. The results presented in this paper could also serve as a reference point to quantify the changes in fish biomass and distributions in the lake.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Similarly, climate change likely affected fish distributions, and as demonstrated here, temperature and precipitation likely affected different species in different manners. However, as indicated in our discussion, our results are still consistent with some recent studies examining the fish distribution patterns, diversity and assemblage structure in the TSL, e.g., [12,19] and elsewhere, such as in the floodplain-lake of the Amazon, where fisheries yields were significantly varied in accordance with the amount of flooded forest habitats [68]. The results presented in this paper could also serve as a reference point to quantify the changes in fish biomass and distributions in the lake.…”
Section: Discussionsupporting
confidence: 93%
“…were distributed from the central to the southern area of the lake. Our findings are consistent, and indeed strengthen the results of previous studies that found floodplain resident or non-migratory fishes were more abundant in the northern section of the lake [12,33,45], the area that is predominantly covered by flooded forest, swampy and shrub land, aquatic vegetation and rice fields [14]. Those floodplain residents spend most of their lifespans in the flooded forest, inhabiting the lake or swamps during the dry season and migrating to the flooded and open areas of the lake during the wet season for spawning and foraging [13].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…During the rainy season, water levels in the TS Lake is highly influenced by floods from the upstream Mekong. A large area of Kampong Chhnang province which is connected to the TS Lake is usually flooded, covering the belt of flooded forests, degraded forests and wetlands surrounding the lake and river (Lieng et al, 1995;Poulsen et al, 2002;Ngor et al, 2018a). These conditions enable the snail species to gain access to breeding and nursing grounds for reproduction and growth, and therefore drive their enormous production during the rainy season.…”
Section: Relationship Between Landing Catches and Water Levels Tempementioning
confidence: 99%